The function of the inter-alpha-trypsin inhibitors in the development of disease - Zhang, Xin-feng; Zhang, Xiao-li; Guo, Li; Bai, Yun-ping; Tian, Yan; Luo, Hua-you (Frontiers in Medicine, 2024)
Through the formation of covalent connections with hyaluronic acid (HA), the Inter-α-trypsin inhibitor (IαI) family collaborates to preserve the stability of the extracellular matrix (ECM). The five distinct homologous heavy chains (ITIH) and one type of light chain make up the IαI family. ITIH alone or in combination with bikunin (BK) has been proven to have important impacts in a number of earlier investigations. This implies that BK and ITIH might be crucial to both physiological and pathological processes. The functions of BK and ITIH in various pathophysiological processes are discussed independently in this paper. In the meanwhile, this study offers suggestions for further research on the roles of BK and ITIH in the course of disease and summarizes the plausible mechanisms of the previous studies.